MENURUNKAN CYCLE TIME STOCK OPNAME IMPORT PARTS DENGAN PATTERN SUPPLY FORM BERBASIS WEBSITE DI ASSEMBLING K-LINE 5 PT ASTRA DAIHATSU MOTOR - Nugraha, Afitro Adam; Rudi Kiswanto; Yohanes C. Sutama; Pramastya Widya Naluri (LPPM Politeknik Astra, 2024)
PT Astra Daihatsu Motor-Engine Plant focuses on producing engines for Daihatsu vehicles and several Toyota vehicles. The Quality Inhouse-Section Audit System Development Department, which focuses on auditing the entire production process, found that the Exicom-Section Import Component Department's KPI had not yet reached the target in the productivity section due to a delay in supply to the k-line 5 assembly. The supply delay was due to the cycle time target of the stock taking process not being achieved (target 40 minutes and actual 63.1 minutes). Then, not achieving the target cycle time of the stock taking process is analyzed using fishbone analysis so that the root cause is found, namely PIC inputs twice for each data, final stock data input to pattern supply sheets and files, stock taking locations (on shelves, dolly transit, and dolly setting), and pattern supply files can only be accessed by a computer in the office import component. The author will address these four root causes with a website-based supply form pattern that will speed up the stock taking process so that the target cycle time (40 minutes) will be achieved